Understanding the Mechanism of Bent DNA Amplifying Sensors Using All-Atom Molecular Dynamics Simulations - Kaitlin Bullard; Deborah Okyere; Shelbi J. Foster; Asmaa A. Sadoon; Jiali Li; Jingyi Chen; Yong Wang (Biosensors)
Bent DNA amplifying sensors were recently developed to amplify and quantify the interactions of DNA with various salts and molecules. However, a thorough quantitative understanding of their mechanism is missing. Here, using all-atom molecular dynamics (MD) simulations, we investigate the behavior and dynamics of sharply bent DNA molecules in the absence and presence of Mg2+ ions at different concentrations. The simulations show that Mg2+ ions reduce the fluctuations of DNA strands, enhance base-pairing, and stabilize bent DNA molecules. The computational results are further verified by both melting curve experiments and ensemble FRET measurements, highlighting the mechanical instability and sensitivity of bent DNA molecules.